Application of the Extended Hildebrand solubility approach applied to mitomycin C in ethanol + water mixtures (2015)
In this work, we applied the extended Hilderband solubility approach (EHSA) to evaluate the solubility of mitomycin C in ethanol-water mixtures at 293.15 K.